Rural–Urban Differences in Suicide Mortality: An Observational Study in Newfoundland and Labrador, Canada: Différences de la Mortalité Par Suicide en Milieu Rural-Urbain: Une Étude Observationnelle à Terre-Neuve et Labrador, Canada. (October 2021) - Reccord, Charlene; Power, Nicole; Hatfield, Keeley; Karaivanov, Yordan; Mulay, Shree; Wilson, Margo; Pollock, Nathaniel
Background: Suicide rates are higher in rural compared to urban areas. Although this pattern appears to be driven by higher rates among men, there is limited evidence about the characteristics of rural people who die by suicide in Canada. The objective of this study was to examine the demographics, manner of death, and social and clinical antecedents of people who died by suicide in rural areas compared to urban areas. Methods: We conducted an observational study of all suicide deaths that occurred among Newfoundland and Labrador residents between 1997 and 2016 using a linked data set derived from a comprehensive review of provincial medical examiner records. We used t tests and χ 2 to assess associations between rural/urban status and variables related to demographics, circumstances, and manner of death, as well as social and medical history. Logistic regression was utilized to assess the independent contribution of any variable found to be significant in univariate analysis. Results: Rural people who died by suicide accounted for 54.8% of all deaths over a 20-year period. Overall, 81.6% of people who died were male. Compared to urban, rural people who died by suicide were younger, more likely to use firearms or hanging, and had a higher mean blood alcohol content at the time of death (27.69 vs. 22.95 mmol/L). Rural people were also less likely to have had a known history of a prior suicide attempt, psychiatric disorder, alcohol or substance abuse, or chronic pain. Discussion: The demographic and clinical differences between rural and urban people who died by suicide underscore the need for suicide prevention approaches that account for place-based differences. A key challenge for suicide prevention in rural communities is to ensure that interventions are developed and implemented in a manner that fits local contexts.